Oligomerization of green fluorescent protein in the secretory pathway of endocrine cells - Renu Jain; Paul B. M. Joyce; Miguel Molinete; Philippe A. Halban; Sven‐Ulrik Gorr (2001)
Green fluorescent protein (GFP) is used extensively as a reporter protein to monitor cellular processes, including intracellular protein trafficking and secretion. In general, this approach depends on GFP acting as a passive reporter protein. However, it was recently noted that GFP oligomerizes in the secretory pathway of endocrine cells. To characterize this oligomerization and its potential role in GFP transport, cytosolic and secretory forms of enhanced GFP (EGFP) were expressed in GH4C1 and AtT-20 endocrine cells. Biochemical analysis showed that cytosolic EGFP existed as a 27kDa monomer, whereas secretory forms of EGFP formed disulphide-linked oligomers. EGFP contains two cysteine residues (Cys49 and Cys71), which could play a role in this oligomerization. Site-directed mutagenesis of Cys49 and Cys71 showed that both cysteine residues were involved in disulphide interactions. Substitution of either cysteine residue resulted in a reduction or loss of oligomers, although dimers of the secretory form of EGFP remained. Mutation of these residues did not adversely affect the fluorescence of EGFP. EGFP oligomers were stored in secretory granules and secreted by the regulated secretory pathway in endocrine AtT-20 cells. Similarly, the dimeric mutant forms of EGFP were still secreted via the regulated secretory pathway, indicating that the higher-order oligomers were not necessary for sorting in AtT-20 cells. These results suggest that the oligomerization of EGFP must be considered when the protein is used as a reporter molecule in the secretory pathway.